Produksi Asi Pada Ibu Postpartum Dengan Pendekatan Etnomedisin Daun Torbangun Di Klinik Surya Medika Way Halim Bandar Lampung - Septi Ristiyana; Margareta Rinjani; Anisa Rina (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2023)
Background: In the physiological state of breastfeeding, the nutritional needs of mothers ncrease because the need for milk to produce breast milk, one of the efforts that can be made to ncrease the rate of excretion and production of breast milk s through the use of traditional medicinal herbs, there are several plants that we believe are good, gradually decrease or have been proven tested. Scientifically increasing the quality and quantity of ASI, for example the foliate plant (Coleus amboinicius) (Ministry of Health, 2016). The formulation of the problem in this research is